Telemedicine Evaluations in Neuro-Ophthalmology During the COVID-19 Pandemic: Patient and Physician Surveys. Issue 3 (September 2021) - Conway, Jenna; Krieger, Penina; Hasanaj, Lisena; Sun, Linus; Scharf, Jackson M.; Odel, Jeffrey G.; Dinkin, Marc J.; Oliveira, Cristiano; Mackay, Devin D.; Rasool, Nailyn; Ko, Melissa; Rucker, Janet C.; et al.
Abstract : Background: The novel coronavirus 2019 (COVID-19) pandemic has transformed health care. With the need to limit COVID-19 exposures, telemedicine has become an increasingly important format for clinical care. Compared with other fields, neuro-ophthalmology faces unique challenges, given its dependence on physical examination signs that are difficult to elicit outside the office setting. As such, it is imperative to understand both patient and provider experiences to continue to adapt the technology and tailor its application. The purpose of this study is to analyze both neuro-ophthalmology physician and patient satisfaction with virtual health visits during the time of the COVID-19 pandemic. Methods: Across three institutions (NYU Langone Health, Indiana University Health, and Columbia University Medical Center), telemedicine surveys were administered to 159 patients. Neuro-ophthalmologists completed 157 surveys; each of these were linked to a single patient visit. Patient surveys consisted of 5 questions regarding visit preparation, satisfaction, challenges, and comfort. The physician survey included 4 questions that focused on ability to gather specific clinical information by history and examination. Results: Among 159 patients, 104 (65.4%) reported that they were satisfied with the visit, and 149 (93.7%) indicated that they were comfortable asking questions. Sixty-eight (73.9%) patients found the instructions provided before the visit easy to understand. Potential areas for improvement noted by patients included more detailed preparation instructions and better technology (phone positioning, Internet connection, and software). More than 87% (137/157) of neuro-ophthalmologists surveyed reported having performed an examination that provided enough information for medical decision-making. Some areas of the neuro-ophthalmologic examination were reported to be easy to conduct (range of eye movements, visual acuity, Amsler grids, Ishihara color plates, and pupillary examination). Other components were more difficult (saccades, red desaturation, visual fields, convergence, oscillations, ocular alignment, and smooth pursuit); some were especially challenging (vestibulo-ocular reflex [VOR], VOR suppression, and optokinetic nystagmus). Clinicians noted that virtual health visits were limited by patient preparation, inability to perform certain parts of the examination (funduscopy and pupils), and technological issues. Conclusions: Among virtual neuro-ophthalmology visits evaluated, most offer patients with appointments that satisfy their needs. Most physicians in this cohort obtained adequate clinical information for decision-making. Even better technology and instructions may help improve aspects of virtual health visits.